2019
DOI: 10.1002/ejoc.201900818
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Azine‐[5]Helicene Hybrids

Abstract: Novel azine‐helicene hybrids (pyridine‐, pyrazine‐ and quinoxaline‐fused along the central ring [5]helicenes) have been prepared in good overall yields through a five‐step synthetic sequence. Commercially available 2,3‐dihaloazines were used as starting materials. To discern the effect of merging an azine moiety within a helical skeleton, the X‐ray structures, UV/Vis absorption spectra, cathodic and anodic electrochemistry of the helicene hybrids were investigated and compared to that of the parent [5]helicene. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 110 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…Apparently, interaction of this type is also realized in solution since the signal of the inner helix proton in the 1 H NMR spectra of azine-fused [6]helicenes appeared in the low field at δ 9.3-9.7 ppm. A similar pattern was observed by us in the structures of the azine-fused [5]helicenes [72].…”
Section: X-ray Molecular Structuressupporting
confidence: 87%
See 3 more Smart Citations
“…Apparently, interaction of this type is also realized in solution since the signal of the inner helix proton in the 1 H NMR spectra of azine-fused [6]helicenes appeared in the low field at δ 9.3-9.7 ppm. A similar pattern was observed by us in the structures of the azine-fused [5]helicenes [72].…”
Section: X-ray Molecular Structuressupporting
confidence: 87%
“…Compound 8b was synthesized in 97% yield by the treatment with a 3-fold excess of ICl on monoiodide 7b. The ICl-induced cyclization of the pyridinebased starting compound 6 proceeded smoothly giving rise to product 7c in 62% ( The fourth step of the synthesis of the target helicenes, namely the Sonogashira coupling of iodides 7a and 7c with p-tolylacetylene, was carried out in the Pd(PPh 3 ) 2 Cl 2 /CuI/Et 3 N/THF catalytic system that proved itself well in the azine-fused [5]helicenes synthesis [72] (Table 4, entries 1 and 3). The corresponding compounds 9a and 9c were obtained in 84 and 88% yields, respectively.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…28 It can also be assumed that the protonation of the inner helix aza group will destabilize molecules 9a and 9b , destroying the C–H⋯N hydrogen bond and disrupting the planarity of their diazahelicene fragments. Indeed, this study and our previous studies 15–18 have shown that diazahelicenes are essentially planar, in contrast to monoaza analogs. It is also known that benzo[ h ]quinoline (p K a = 10.84 (MeCN) and 4.25 (H 2 O)) is a weaker base by 1.82 p K a units in MeCN and 1.37 units in water compared to isomeric acridine.…”
Section: Resultssupporting
confidence: 71%